Malignant Skin Tumors of The Periorbital Region: a Retrospective Study - Demir, Canser Y.; Köhle, Ülkü (Fırat University, 2003)
Aim: To evaluate the clinical characteristics of malignant skin tumors on the periorbital region and our surgical results. Materials and method: A retrospective study was used to review patients who had malignant periorbital skin tumors and underwent surgery from 1997 to 2003. Surgical excision and various reconstructive procedures were performed for the treatments of these tumors. Results: We reviewed 54 patients with malignant skin tumor on their periorbital region. Their mean age was 63.5 ± 10.15 years (range 32 to 89 years) and 59.3% were male (32 cases), 40.7% were female (22 cases). The tumors, in order of frequency, were basal cell carcinoma (38 cases, 70.3%), squamous cell carcinoma (10 cases, 18.5%), sebaceous gland adenocarcinoma (4 cases, 7.4%) and malignant melanoma (2 cases, 3.7%). The most of the lesions involved around the lower lid (30 cases, 55.56%). Reconstruction of the surgical defects were performed during the same operations. Five patients (9.26%) had local recurrence. Two patients (3.7%) were died from lung small cell carcinomas. Two (3.7%) exenterations were performed. Distant metastases were not found in patients. Conclusion: Periorbital region skin tumors are common, and potentially fatal diseases. However, if detected early and treated adequately, the prognosis is generally excellent. Because presentation varies and histological examination is required for accurate diagnosis, any suspicious lesion occurring on the periorbital region should be excised or biopsied.

Amaç: Periorbital bölgedeki malign cilt tümörlerinin klinik özelliklerini ve cerrahi sonuçlarımızı değerlendirmek. Gereç ve yöntem: 1997-2003 yılları arasında periorbital bölgesinde malign cilt tümörü nedeniyle cerrahi tedavi görmüş hastalar retrospektif olarak incelendi. Tümörlerin tedavisinde cerrahi eksizyon ve çeşitli rekonstrüktif girişimler uygulandı. Bulgular: Periorbital bölgesinde malign cilt tümörü bulunan 54 hastayı gözden geçirdik. Hastaların ortalama yaşı 63.5 ± 10.15 yıl (dağılım 32-89 yıl), %59.3'ü erkek (32 hasta), %40.7'si (22 hasta) kadın idi. Sıklık sırasına göre bazal hücreli karsinom (38 hasta, %70.3), skuamöz hücreli karsinom (10 hasta, %18.5), sebase gland adenokarsinomu (4 hasta,%7.4) ve malign melanoma (2 hasta, %3.7) ile karşılaşıldı. Lezyonların çoğu alt gözkapağı ve çevresinde yerleşmişti (30 hasta, %55.56). Cerrahiye bağlı gelişen defektlerin rekonstrüksiyonu aynı seansta yapıldı. Beş hastada (%9.26) lokal rekürrens görüldü. İki hasta (%3.7) akciğer küçük hücreli kanseri nedeniyle kaybedildi. İki hastada (%3.7) ekzenterasyon yapıldı. Hastalarda uzak metastaz tespit edilmedi. Sonuç: Periorbital bölge malign cilt tümörleri sık rastlanılan ve ölümcül sonuçlar doğurabilen bir hastalık grubudur. Bununla birlikte erken farkına varılır ve uygun bir şekilde tedavi edilirlerse prognozları çok iyidir. Çok farklı şekillerde karşımıza çıkabilmeleri ve kesin tanı konması için bu bölgedeki her şüpheli lezyonun eksizyonu ile histolojik incelemesinin yapılması gerekir.
Periorbital Bölge Malign Cilt Tümörleri: Retrospektif Çalışma